BENTUK MEMPERHATIKAN dan MEMERKOSA - Amas Suryadi (Jurnal Sosioteknologi, 2009)
Based on morphology, Languages in the world can be classified into four types: agglutination, flexi, isolation, and incorporation. In the language of agglutination such as Indonesian, there is what-so-called morphophonemic, i.e. the change of sound caused by affixation. One of the features is having prefix me(ng)- on the base verb initiated by phoneme /p/ that turns into phoneme /m/ by the term of assimilation, such as memercayai, not mempercayai. Different from the form memperhatikan, this form comes from the word hati that receives prefix per-, which turns into perhati as the base word. Here per- is not the initial phoneme of base word, but the initial phoneme of base form, so that it is not assimilated. It is also different from the form memerkosa which comes from the base word perkosa. Here per-is not a prefix but a syllable. Key words: morphology, morphophonemic, assimilation